Kondisi Fisik Pemain Bola Voli Klub di Kota Lubuklinggau - Ever Sovensi; Muhammad Supriyadi; Muhammad Suhdy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The research objective was to determine the physical condition of Club Caroline volleyball players and Lubuklinggau City Club JVC in 2018. This type of research was descriptive quantitative. The population of this study were male volleyball players Club Caroline and Lubuklinggau City Club JVC with all 45 players, consisting of 25 Club Caroline players and 20 Club JVC players. The sample in this study amounted to 45 players, which were taken using total sampling technique. The results of this study explained that the explosive strength of leg muscles possessed by Caroline club volleyball players averaged 108.23 categorized as Enough, while the average explosive power level the limbs owned by JVC club volleyball players are 115.18 categorized Good. Furthermore, the endurance test results possessed by Carolin club volleyball players an average of 32.6 are categorized sufficient, while the average endurance level possessed by Caroline Club volleyball players is 37.7 categorized as moderate. Conclusion, the explosive strength of limb muscles of the Caroline club volleyball player is categorized enough and the explosive strength of the leg muscles of the JVC club players is categorized as good. The durability of Caroline's club volleyball players is categorized enough and those possessed by JVC Club volleyball players are categorized as being moderate. Furthermore, the speed of Caroline club volleyball players and JVC is good. Whereas the agility of the Caroline club players is categorized as good and the agility of the JVC club volleyball players is categorized as Moderate. Furthermore, the abdominal muscle strength of club volleyball players Caroline and JVC entered the Good category. Keywords: Physical Condition, Bolavoli